New Medications in the Treatment of Peanut Allergy - Walker, Scot (Hosp Pharm, 2018)
In the general population, the prevalence of peanut allergy has remained stable at 1.3%. However, in children, the prevalence appears to be increasing. There are no approved treatments for peanut allergy so current treatment involves educating the patient on avoiding products that contain peanut protein. Two drugs that allow controlled desensitization with controlled amounts of peanut protein have reached late stages of development.